Sistem Informasi Administrasi Surat Berbasis Web Pada Kantor Desa Menerapkan Metode Waterfall - Setiawan, Aris; Rahman Kadafi, Abdul (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
A web-based mail administration information system is used to manage the administrative service process for submitting correspondence. The process of submitting correspondence to Rojopolo Village is still done manually using the Microsoft Word application. The obstacle faced by service officers is when they need data reports on letter submissions from residents, because letter data is only in the form of archival paper which carries the risk of losing data, besides that the manual letter submission process takes a long time so that the letter administration service is less effective and efficient. To overcome this problem, a Web-based Mail Administration Information System will be built at the Rojopolo Village Office so that it can improve the performance of the village service department in processing data so that services are more effective and efficient. The system development method uses the waterfall method and system design uses unifield modeling language (UML) diagrams. Based on the results of black box testing, the features built (such as letter submission, letter list, population registration, master data, reports) work 100%. The system was built using the Visual Basic .Net programming language and MSSQL Server database.